ANALISIS BENTUK KELEMBAGAAN KELOMPOK TANI HUTAN RAKYAT DESA GATTARENG KECAMATAN MARIORIWAWO KABUPATEN SOPPENG - . Yusran; Muhammad Alif; Muh. Aswan; Adrayanti Sabar (Universitas Tanjungpura, 2019)
This present research aims to identify related actor, in the formation and development farmers by the format rules, format relation and important role management of people forests in the village of Gattareng. The result of this research is to give inforaton for the farmers about Institutional Form analysis of the people forests by the form, format relation and important role management of the people forests. In addition, this research is conducted in October – November 2017. The research site is in gattareng village, Marioriwawo district, Soppeng regency. The methods of data collection used in this research are observation and interview. Based on research results it was concluded that related actor in establishment and development farmers of the people forests is the farmers, village head in the village of Gattareng, Forestry service in soppeng regency and the peopleof the farmers. In the formation Baccewe farmers the village of gattareng Mr. Bide is the had of the farmers make a formal role and activties by Baccewe farmers. The formal role of Baccewe Farmers is, the membership of farmers where in the membership must have a farmers, meeting for the membership of the farmers must twice for a week and all of the applicable regulation have a sanctions. Important role the management of people forests in the Village of Gattareng basically for public welfare of the people around the forests. Forestry service and agriculture servise in Soppeng regency do sustainable development of forest resources. By doing policy forest management optimize premises active engagement from people around the forest whose life depends on the forest. The goal is to improve people’s welfareKeyword: Farmers, Institutional, People Forests